Parasite dilution improves lamb growth more than does the complementarity of forage niches in a mesic pasture grazed by sheep and cattle - Joly, Frédéric; Note, Priscilla; Barbet, Marc; Jacquiet, Philippe; Faure, Sandrine; Benoit, Marc; Dumont, Bertrand (Frontiers in Animal Science, 2022)
Agroecological practices can improve the functioning of livestock farming systems by optimizing their underlying biological processes. Sheep/cattle mixed-grazing is an example of such a practice in which sheep grazing with cattle can achieve a higher liveweight gain (LWG), than sheep grazing alone. We conducted an experiment to assess the relative roles of parasite dilution and forage niche complementarity in improving sheep LWGs. We used continuous grazing and compared the LWGs of 5- to 9-month ewe lambs, grazing alone or with heifers, at two contrasted sheep/cattle ratios (~50/50% and 20/80% in livestock units). The animals were not treated for strongyles (gastrointestinal parasites) before or during the experiment. We assessed parasitism by counting the number of strongyle eggs excreted per gram of faeces (EPG) and evaluated the forage niche complementarity through observations of feeding behaviour, combined with measurements of faecal nitrogen content (N). We observed that i) the diet was moderately improved by mixed-grazing (+4% of dicots and +11% young vegetative grass at most, but these improvement were not statistically significant (resp. P=0.28 and P=0.35); ii) N levels were not significantly different across treatments (~2%; P=0.156); iii) EPGs were ~50% lower for mixed-grazing than for monospecific grazing (545 and 716 vs. 1278, P<0.01), iv) LWGs were much higher for mixed-grazing than for monospecific grazing (~40 g per day higher, P<0.001); and v) LWGs and EPG did not significantly differ between the two sheep/cattle ratios studied (resp. P=0.91 and P=0.56). We thus attributed most of the improved ewe lamb LWGs in our experiment to parasite dilution rather than to forage niche complementarity. In addition, the similar EPG and LWG observed suggest that the benefits of mixed-grazing can be obtained easily, i.e. over a wide range of sheep/cattle ratios. Based on the definition of the adjective operable (‘capable of being put into use, operation or practice’), we also conclude that mixed-grazing seems an operable practice from a biological viewpoint.